Towards a cost effective strategy for cutinase production by a recombinant Saccharomyces cerevisiae: strain physiological aspects - Ferreira, Bruno S. (2020)
Although the physiology and metabolism of the growth of yeast strains has been extensively studied, many questions remain unanswered where the induced production of a recombinant protein is concerned. This work addresses the production of a Fusarium solani pisi cutinase by a recombinant Saccharomyces cerevisiae strain induced through the use of a galactose promoter. The strain is able to metabolise the inducer, galactose, which is a much more expensive carbon source than glucose. Both the transport of galactose into the cell—required for the induction of cutinase production—and galactose metabolism are highly repressed by glucose. Different fermentation strategies were tested and the culture behaviour was interpreted in view of the strain metabolism and physiology. A fed-batch fermentation with a mixed feed of glucose and galactose was carried out, during which simultaneous consumption of both hexoses was achieved, as long as the glucose concentration in the medium did not exceed 0.20 g/l. The costs, in terms of hexoses, incurred with this fermentation strategy were reduced to 23% of those resulting from a fermentation carried out using a more conventional strategy, namely a fed-batch fermentation with a feed of galactose.